Endomyocardial fibrosis in a 7-year-old Nigerian child: a case report and review of the literature - Bassey, Kevin; Okpokowuruk, Frances Sam; Oghenedoro, Osafugbe (International Journal of Scientific Reports, 2022)
Endomyocardial fibrosis (EMF) is a poorly-understood idiopathic disorder characterized by the development of restrictive cardiomyopathy. It is a disorder of the tropics and subtropics and was once the second commonest cause of acquired heart disease in Nigeria. Its diagnosis is often made when the disease is advanced and the prognosis is invariably poor at this stage. Reports of EMF have become increasingly rare in recent years and it is frequently misdiagnosed. This report seeks to highlight EMF as a still present and potentially important cause of heart failure in Nigerian children. A 7-year-old male referred to the pediatric cardiology clinic with complaints of abdominal and facial swelling, with no difficulty in breathing and exercise intolerance. Examination revealed a classic “egg-on-stick” appearance. Apex was not displaced and heart sounds were distant. Liver was enlarged but non tender and there was demonstrable ascites. A 2D echocardiography showed massive right atrial enlargement with severe tricuspid regurgitation and fibrosis within the right ventricular cavity which was small. There was a moderate-sized pericardial effusion. Electrocardiogram showed right atrial enlargement with low-voltage complexes. Full blood count showed eosinophilia (20% total white blood cell count). Total serum protein and albumin were reduced. EMF, though increasingly rare, remains an important cause of childhood cardiac morbidity and mortality. A high index of suspicion is critical as the prognosis remains poor.